Multiple adverse outcomes following first discharge from inpatient psychiatric care: a national cohort study. (July 2019) - Walter, Florian; Carr, Matthew J; Mok, Pearl L H; Antonsen, Sussie; Pedersen, Carsten B; Appleby, Louis; Fazel, Seena; Shaw, Jenny; Webb, Roger T
Summary: Background: Discharged psychiatric inpatients are at elevated risk of serious adverse outcomes, but no previous study has comprehensively examined an array of multiple risks in a single cohort. Methods: We used data from the Danish Civil Registration System to delineate a cohort of all individuals born in Denmark in 1967–2000, who were alive and residing in Denmark on their 15th birthday, and who had been discharged from their first inpatient psychiatric episode at age 15 years or older. Each individual in the discharged cohort was matched on age and sex with 25 comparators without a history of psychiatric admission. Data linked to each individual were also obtained from the Psychiatric Central Research Register, Register of Causes of Death, National Patient Register, and the National Crime Register. We used survival analysis techniques to estimate absolute and relative risks of all-cause mortality, suicide, accidental death, homicide victimisation, homicide perpetration, non-fatal self-harm, violent criminality, and hospitalisation following violence, until Dec 31, 2015. Findings: We included 62 922 individuals in the discharged cohort, and 1 573 050 matched comparators. Risks for each of all eight outcomes examined were markedly elevated in the discharged cohort relative to the comparators. Within 10 years of first discharge, the cumulative incidence of death, self-harm, committing a violent crime, or hospitalisation due to interpersonal violence was 32·0% (95% CI 31·6–32·5) in the discharged cohort (37·1% [36·5–37·8] in men and 27·2% [26·7–27·8] in women). Absolute risk of at least one adverse outcome occurring within this timeframe were highest in people diagnosed with a psychoactive substance use disorder at first discharge (cumulative incidence 49·4% [48·4–50·4]), and lowest in those diagnosed with a mood disorder (24·4% [23·6–25·2]). For suicide and non-fatal self-harm, risks were especially high during the first 3 months post-discharge, whereas risks for accidental death, violent criminality, and hospitalisation due to violence were more constant throughout the 10-year follow-up. Interpretation: People discharged from inpatient psychiatric care are at higher risk than the rest of the population for a range of serious fatal and non-fatal adverse outcomes. Improved inter-agency liaison, intensive follow-up immediately after discharge, and longer-term social support are indicated. Funding: Medical Research Council, European Research Council, and Wellcome Trust.